회전근개 파열의 건-골 경계면의 치유를 강화하기 위한 현재와 미래의 전략들 - 김동현(Dong Hyun Kim); 윤지욱(Jee Wook Yoon); 윤종필(Jong Pil Yoon) (The journal of the Korean Orthopaedic Association, 2022)
회전근개 파열의 봉합 후 건-골 경계면에서의 치유는 견관절 분야에서 중요한 과제이며, 건-골 경계면에서 적용할 수 있는 생물학적인 보강재들에 대한 임상적, 실험적인 연구가 활발히 진행되고 있다. 본 종설에서는 현재 회전근개 파열에서 골과 이식편의 경계면에서 치유력을 강화하기 위해 시도되고 있는 다양한 생물학적인 보강재의 임상적, 실험적 결과와 유용성에 대해 알아보고자한다. Healing at the tendon-to-bone interface after rotator cuff repair is an essential aspect of management for shoulder surgeons. Many notable treatment methods have been proposed to promote healing at the tendon-to-bone interface after rotator cuff repair. Therefore, we review the clinical and experimental results of various methods and materials that are being tested to enhance healing in the bone-to-graft interface. KCI Citation Count: 0